2014
DOI: 10.1007/s00289-014-1162-x
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation of polylactide with carboxyl groups at one chain end in the presence of metal cations

Abstract: Polylactides with one or more carboxyl groups at one chain end were synthesized by cationic polymerization according to activated monomer mechanism and by application of ''thiol-yne'' click chemistry for subsequent functionalization. End groups of such obtained polylactides were converted into ionic groups by neutralization of polymer solutions with metal oxides, mainly calcium oxide, and the aggregation of individual stereoisomers as well as that of the mixture of poly(Llactide) (PLLA) and poly(D-lactide) (PD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…The possibility of the regulation of PLA stereocomplex morphology by the nature of the end groups was also noticed in our study on the aggregation of aliphatic polyesters (among them PLA stereoisomers) performed in the presence of metal ions …”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…The possibility of the regulation of PLA stereocomplex morphology by the nature of the end groups was also noticed in our study on the aggregation of aliphatic polyesters (among them PLA stereoisomers) performed in the presence of metal ions …”
Section: Introductionsupporting
confidence: 65%
“…Thus, in the present paper studies of the stereocomplexation of linear PLAs containing different numbers and placement of carboxyl groups performed in solution in the presence of metal cations, mainly Ca 2+ (which is considered most interesting for possible biomedical applications), leading to regular microspheres are presented. PLAs were obtained by cationic ring‐opening polymerization (ROP) as described earlier . The morphology of microparticles obtained by stereocomplexation (analyzed by SEM) is described depending on the PLA used and the solvent.…”
Section: Introductionmentioning
confidence: 99%
“…The viscosity of the stereocomplexed gels was determined by a Brookfield DV‐II Viscometer on 12 wt% polymer solutions that contained equimolar amounts of 6‐arm ‐ PLLA and 6‐arm‐PDLA enantiomers functionalized with OH and COOH end groups, respectively. The viscosity of the stereocomplex PLA‐gel terminated with carboxylic groups is 34.5 Pa s −1 , and it is almost two times higher than the viscosity of the gel composed of 6‐arm‐PLA‐OH, which is equal to 19.9 Pa s −1 .…”
Section: Resultsmentioning
confidence: 99%
“…When a process is conducted without the removal of condensation water, the water molecules can initiate the ROP of the cyclic ester, leading to macromolecules with an AB-type functionality (instead of AB 2 -type), thereby lowering the degree of branching. This phenomenon was observed in the case of the cationic ring-opening polymerization of lactide performed in the presence of hydroxyacid [115].…”
Section: Scheme 12mentioning
confidence: 79%
“…For example, it was observed that in the later stages of the polymerization of LA and CL initiated by hydroxyacid (or at higher catalyst concentrations), condensation reactions with the participation of carboxyl groups originated from bisMPA occurred [110]. The undesired condensation reaction between terminal hydroxyl and carboxyl groups was also observed in the case of the cationic polymerization of LA initiated by hydroxyacids [115].…”
Section: Pla-based Macromonomers Could Be Used For Polycondensation Wmentioning
confidence: 93%